The Bethesda System for Reporting Thyroid Cytopathology Definitions, Criteria, and Explanatory Notes (Springer International Publishing, 2018)
The first edition of The Bethesda System for Reporting Thyroid Cytopathology was published in 2010 and has greatly influenced the practice of thyroid cytopathology. The terminology proposed and illustrated in this text has been widely adopted not only in the U.S. but also abroad. It has become an essential text for pathology trainees and practicing pathologists examining thyroid fine needle aspiration (FNA) specimens. Since 2010, there have been a number of important advances in the management of patients with nodular thyroid disease and in the understanding of the biology of thyroid cancer. This new edition includes these advances that impact terminology for reporting thyroid cytopathology. In particular, it incorporates a discussion of the recently implemented and now widespread use of molecular testing of thyroid FNA samples, which has transformed the management of patients with nodular thyroid disease in the U.S.. In addition, this edition accommodates the recent changes to the classification of thyroid cancer, most notably the introduction of a new thyroid diagnosis, that of "non-invasive follicular tumor with papillary-like nuclear features (NIFTP)". Thoroughly revised and updated, The Bethesda System for Reporting Thyroid Cytopathology, Second Edition will provide the reader with a unified approach to diagnosing and reporting thyroid FNA interpretations. It serves as a reference guide not just for pathologists, but also endocrinologists, surgeons, and radiologists.